PLATELET ACTIVATION AND AGGREGATION BY GAS BOBBLES IN VITRO - Thorsen, Terje; Holmsen, Holm (Thrombosis and Haemostasis, 1987)
After diving, in decompression sickness and after extra-corporeal circulation in membrane oxygenators, there is often a reductionin the number of circulating platelets. Gas bubbles seem to be the common denominator for these quite different conditions, and it is assumed that gas bubbles activate the platelets although by unknown mechanisms. We have used gas bubbles as a platelet agonist in an aggregometer-like apparatus. The bubbles produced platelet aggregation similar to that caused by "classical" agonists,e.g.,ADP, epinephrine etc. The gas-liquidinterface was essential for this aggregation,and the bubble diameter, rather than thetype of gas or the total number of bubbles, determined the potency of this agonist. Electron microscopical studies revealed that singleplatelets and platelet aggregates with numerous, short pseudopods adhered to the bubble wall. The platelet aggregation caused bygas bubbles was abolished by metabolic blockers (2-deoxyglucose and antimycin A), EGTA,phosphodiesterase inhibitors (theophylline, caffeine, papaverine, dipyridamole), adenylate cyclase activators (PGE1 adenosine, AMP), or a combination of low concentrationsof phosphodiesterase inhibitors and adenylate activators. Theophylline which is regardedas a weak inhibitor of platelet activation in general, was an especially potent inhibitor of gas bubble-induced platelet aggregationwhereas cyclooxygenase inhibitors (acetyl salicylic acid, indomethacin), adrenoreceptor blocker (yohimbine), guanylate cyclase activators (azide, jiitroprusside) and trifluoperazine had little or no effect. Bubble-induced,aggregation is thus similar to theprimary,and not the secondary, aggregation caused byclassical agonists. However, the ineffectiveness of guanylate cyclase activators distinguishes bubble-induced aggegation from "classical" primary aggregation.